Management of Adult Primary Immune Thrombocytopenia: Delphi- Based Consensus Recommendations - Ahmet Muzaffer Demir; Elif Gülsüm Ümit; Muhlis Cem Ar; Mesut Ayer; Meltem Aylı; Volkan Karakuş; Emin Kaya; Fahir Özkalemkaş; Nilgün Sayınalp; Mehmet Sönmez; Fahri Şahin; Selami Koçak Toprak; et al. (Turkish Journal of Hematology, 2024)
Objective: Primary immune thrombocytopenia (pITP) is an acquired autoimmune disorder related to the increased destruction and/or impaired production of platelets. Its diagnosis and management are challenging and require expertise and the interpretation of international consensus reports and guidelines with national variations in availability. We aimed to assess the agreement of hematologists in Türkiye on certain aspects of both first-line and second-line management of patients with pITP. Materials and Methods: Applying a modified Delphi method, the Turkish National ITP Working Group (14 steering committee members), founded under the auspices of the Turkish Society of Hematology, developed a 21-item questionnaire consisting of statements regarding the first-line and second-line treatment of pITP. A total of 107 adult hematologists working in either university or state hospitals voted for their agreement or disagreement with the statements in two consecutive rounds. Results: The participants reached consensus on the use of corticosteroids as first-line treatment and with limited duration. Methylprednisolone was the corticosteroid of choice rather than dexamethasone. Use of intravenous immunoglobulin was not preferred for patients without bleeding. It was also agreed that thrombopoietin receptor antagonists (TPO-RAs) or rituximab should be recommended as second-line treatment and that splenectomy could be considered 12-24 months after diagnosis in patients with chronic pITP. Conclusion: The optimization of the dose and duration of TPO-RAs in addition to corticosteroids is necessary to improve the management of patients with pITP.